Clinical Risk Factors of Licorice-Induced Pseudoaldosteronism Based on Glycyrrhizin-Metabolite Concentrations: A Narrative Review - Yoshino, Tetsuhiro; Shimada, Saori; Homma, Masato; Makino, Toshiaki; Mimura, Masaru; Watanabe, Kenji (Frontiers in Nutrition, 2021)
Licorice, the dried root or stolon of Glycyrrhiza glabra or G. ularensis, is commonly used worldwide as a food sweetener or crude drug. Its major ingredient is glycyrrhizin. Hypokalemia or pseudoaldosteronism (PsA) is one of the most frequent side effects of licorice intake. Glycyrrhizin metabolites inhibit type 2 11β-hydroxysteroid dehydrogenase (11βHSD2), which decomposes cortisol into inactive cortisone in the distal nephron, thereby inducing mineralocorticoid receptor activity. Among the several reported glycyrrhizin-metabolites, 18β-glycyrrhetyl-3-O-sulfate is the major compound found in humans after licorice consumption, followed by glycyrrhetinic acid. These metabolites are highly bound to albumin in blood circulation and are predominantly excreted into bile via multidrug resistance-associated protein 2 (Mrp2). High dosage and long-term use of licorice are constitutional risk factors for PsA. Orally administered glycyrrhizin is effectively hydrolyzed to glycyrrhetinic acid by the intestinal bacteria in constipated patients, which enhances the bioavailability of glycyrrhizin metabolites. Under hypoalbuminemic conditions, the unbound metabolite fractions can reach 11βHSD2 at the distal nephron. Hyper direct-bilirubin could be a surrogate marker of Mrp2 dysfunction, which results in metabolite accumulation. Older age is associated with reduced 11βHSD2 function, and several concomitant medications, such as diuretics, have been reported to affect the phenotype. This review summarizes several factors related to licorice-induced PsA, including daily dosage, long-term use, constipation, hypoalbuminemia, hyper direct-bilirubin, older age, and concomitant medications.